Unconventional Non-Invasive Diagnostic Techniques and Treatment of White Spot Lesions in Paediatric Dentistry and Orthodontics - Ogodescu Alexandru; Igna Andreea; Ogodescu Emilia; Luca Magda (European Scientific Journal, ESJ, 2017)
Minimal Intervention Dentistry (MID), a concept that aims to minimize the interventional procedures applied on teeth affected by dental caries, emphasizes the importance of prevention and detection of lesions in early stage. The white spot lesion (WSL) is the first visible stage of the carious process, affecting the enamel. Their detection and treatment has been significantly improved in the last decade through new technology available. Our paper describes a non-invasive detection method, using a lighttransmission device (transillumination of the teeth using Diagnocam, by Kavo) , combined with a resin infiltration technique (using Icon, by DMG) of the WSL.